2013
DOI: 10.1021/am400695e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fullerene Tris-adducts on the Photovoltaic Performance of P3HT:Fullerene Ternary Blends

Abstract: Fullerene tris-adducts have the potential of achieving high open-circuit voltages (V(OC)) in bulk heterojunction (BHJ) polymer solar cells (PSCs), because their lowest unoccupied molecular orbital (LUMO) level is higher than those of fullerene mono- and bis-adducts. However, no successful examples of the use of fullerene tris-adducts as electron acceptors have been reported. Herein, we developed a ternary-blend approach for the use of fullerene tris-adducts to fully exploit the merit of their high LUMO level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 65 publications
5
61
0
Order By: Relevance
“…The I-V characteristics of the OFETs of the ICBA derivatives are summarized in Table 4. The ICBA devices exhibited an average electron mobility of 3.40×10 −3 cm 2 V −1 s −1 , which agreed well with the previous findings [42]. The average electron mobility of FICBA devices was 9.97×10 −4 cm 2 V −1 s −1 , and the maximum electron mobility (μ e, max = 1.03×10 −3 cm 2 V −1 s −1 ) was comparable to that of the ICBA devices.…”
Section: February 2015supporting
confidence: 90%
See 1 more Smart Citation
“…The I-V characteristics of the OFETs of the ICBA derivatives are summarized in Table 4. The ICBA devices exhibited an average electron mobility of 3.40×10 −3 cm 2 V −1 s −1 , which agreed well with the previous findings [42]. The average electron mobility of FICBA devices was 9.97×10 −4 cm 2 V −1 s −1 , and the maximum electron mobility (μ e, max = 1.03×10 −3 cm 2 V −1 s −1 ) was comparable to that of the ICBA devices.…”
Section: February 2015supporting
confidence: 90%
“…Therefore, systematic study of the effects of the molecular structure of fullerene derivatives on their interaction with conjugated polymers and of their effects on the performances of PSCs is essential to determine the appropriate design of fullerene derivatives for use in PSCs. Such study on the molecular structure-device function relationship in PSCs using the indene-C 60 bis-adducts (ICBA) model is especially important, because ICBA is one of the most studied and successful bis-adduct fullerenes, which produces high V oc and PCE values in PSCs [33,35,42].…”
Section: February 2015mentioning
confidence: 99%
“…24,30,31 Therefore, the majority of studies on ternary solar cells have focused on multi-polymer donor:acceptor blends. 19,23,[27][28][29] However, the mixing of two polymers is more complicated due to both a lack of entropic driving force for mixing, and the potential for strong intermolecular attractions between polymer chains. 32 Therefore, a ternary approach, wherein small molecule acceptors are mixed in a donor:multi-acceptor blend (D:A1:A2, where D is donor polymer, A1 is the primary acceptor and A2 is a second acceptor), has the potential to offer morphological advantages.…”
Section: Introductionmentioning
confidence: 99%
“…The cascade like energy levels (shown in Fig. 4) of ternary blend PSCs can facilitate charge transfer at the D/A interface owing to the bridging effect to reduce the energy loss [31,32]. For example, Huang et al [33] reported that by incorporating a small molecule donor 7,7'-{5,5'- [10,12-…”
Section: More Efficient Charge Transfer and Charge Transportmentioning
confidence: 99%
“…Ternary blend devices with 15% ICBA content exhibit an average PCE of 8.13%, higher than that (7.23%) of the PTB7:PC 71 BM binary blend. Kang et al [32] used fullerene tris-adducts to fully exploit the merit of their high LUMO level. The compound OXCTA was used as a ternary acceptor in the model system of P3HT as the electron donor and fullerene monoadduct as the acceptor.…”
Section: One Polymer Donor and Two Acceptors (D-a 1 -A 2 ) Systemmentioning
confidence: 99%